Persistent high-latitude ionospheric response to solar wind forcing - Borries, Claudia; Iochem, Pelin; Tasnim, Samira; Davis, Fredy (Journal of Space Weather and Space Climate, 2024)
The solar wind continuously transfers energy into the Earth’s thermosphere-ionosphere system and variations in the solar wind properties modify the state of the system. The modifications are best visible during storm conditions when the ingestion of extreme amounts of solar wind energy into the thermosphere-ionosphere system causes global changes in thermosphere as well as large deviations in the ionospheric electron density from its quiet conditions. This study shows that there exists a persistent impact of the solar wind on the high-latitude electron density. A data set of 22 years of Total Electron Content (TEC) and 15 years of ionosonde data (critical frequency foF2 and height of maximum electron density hmF2) at Tromsø (70°N, 19°E) are used for correlation analyses with different solar wind parameters from OMNIWEB hourly “Near-Earth” solar wind magnetic field and plasma data. The results show that the ionospheric parameters systematically respond with an increase or decrease depending on local time, season, and solar cycle. TEC and foF2 increase with solar wind energy during winter night conditions and decrease with increasing solar wind energy during summer daytime. The summer negative ionospheric response is more intense during high solar activity conditions, while the winter positive ionospheric response is stronger during low solar activity. An anomaly is observed around 10 UT (noon) when TEC and foF2 respond with an increase during low solar activity conditions. Plasma convection, particle precipitation and Joule heating are the main drivers of the observed electron density changes at Tromsø. Local time, season, and solar cycle changes in the background ionosphere-thermosphere conditions lead to different effects of these driving processes. The results help to better understand the variability of the high-latitude electron density and show that solar wind forcing causes a systematic and persistent response of the ionosphere, which alternates depending on local time, season, and solar cycle.